Prime Spot

x 2 + x y + y 2 = z 2 x^2 + xy + y^2 = z^2

Let x , y , x,y, and z z be prime numbers satisfying the equation above. What is the largest possible product x y z ? xyz?


Inspired by Ptolemy's Riddle II


The answer is 105.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Patrick Corn
Jan 17, 2017

Rewrite as ( x + y ) 2 x y = z 2 , (x+y)^2-xy = z^2, or ( x + y ) 2 z 2 = x y . (x+y)^2-z^2 = xy. This factors: ( x + y z ) ( x + y + z ) = x y . (x+y-z)(x+y+z) = xy. Because x x and y y are prime, x y xy has only the following factors: 1 , x , y , x y . 1,x,y,xy.

The factor x + y + z x+y+z is strictly bigger than x x and y , y, so it must be x y . xy. Then x + y z x+y-z has to be 1. 1. Adding these equations gives 2 ( x + y ) = x y + 1 , 2(x+y)=xy+1, which simplifies in the usual way to ( x 2 ) ( y 2 ) = 3. (x-2)(y-2)=3. The only solutions in prime numbers (indeed, positive integers) x , y x,y are 3 , 5 3,5 and 5 , 3 , 5,3, which leads to z = 7. z=7. So the maximum (indeed, the only) product is x y z = 105 . xyz=\fbox{105}.

I got to the factors of xy but then I gave up as it was time to sleep :(

Shubhrajit Sadhukhan - 7 months ago

This was very helpful -- thank you!

Lisa Liu - 7 months ago

Relevant wiki: Quadratic Diophantine Equations - Solve by Factoring

Let f ( x , y , z ) : x 2 + x y + y 2 = z 2 f(x,y,z): x^2 + xy + y^2 = z^2 .

Then x 2 + x y + ( y 2 z 2 ) = 0 x^2 + xy + (y^2 - z^2) = 0

The quadratic residue must then be perfect square: y 2 4 ( y 2 z 2 ) = n 2 y^2 -4(y^2 - z^2) = n^2 for some integer n n .

Thus, 4 z 2 3 y 2 = n 2 4z^2 - 3y^2 = n^2 .

4 z 2 n 2 = 3 y 2 4z^2 - n^2 = 3y^2

( 2 z n ) ( 2 z + n ) = 3 y 2 (2z-n)(2z+n) = 3y^2

Since we are looking for prime numbers x , y , z x, y, z , there are only three possible factorization for 3 y 2 3y^2 :

  1. 3 y 2 = 1 × 3 y 2 3y^2 = 1\times 3y^2

  2. 3 y 2 = y × 3 y 3y^2 = y\times 3y

  3. 3 y 2 = 3 × y 2 3y^2 = 3\times y^2

For the first scenario, if 3 y 2 = 1 × 3 y 2 3y^2 = 1\times 3y^2 , then 2 z + n = 3 y 2 2z+n = 3y^2 and 2 z n = 1 2z-n = 1 .

Then n = 2 z 1 n = 2z - 1 .

Hence, 4 z 2 n 2 = 4 z 2 ( 2 z 1 ) 2 = 4 z 1 = 2 n + 1 = 3 y 2 4z^2 - n^2 = 4z^2 - (2z-1)^2 = 4z - 1 = 2n + 1 = 3y^2

n = 3 y 2 1 2 n =\dfrac{3y^2 - 1}{2}

Then x = n y 2 = 3 y 2 2 y 1 4 = ( 3 y + 1 ) ( y 1 ) 4 x = \dfrac{n - y}{2} = \dfrac{3y^2 - 2y -1}{4} = \dfrac{(3y+1)(y-1)}{4} .

Since x x is prime, there are only three possible factorizations for the right terms:

I. 3 y + 1 = 4 x 3y+1 = 4x and y 1 = 1 y-1 = 1 . In this case, y = 2 y = 2 , but that will result in x = 7 4 x = \dfrac{7}{4} , which is not a prime integer.

II. 3 y + 1 = x 3y+1 = x and y 1 = 4 y-1 = 4 . In this case, y = 5 y = 5 , but that will result in x = 16 x = 16 , which is not a prime integer.

III. 3 y + 1 = 2 x 3y+1 = 2x and y 1 = 2 y-1 = 2 . In this case, y = 3 y = 3 , and that leads to x = 5 x=5 and z 2 = 5 2 + 5 × 3 + 3 2 = 49 z^2 = 5^2 + 5\times 3 + 3^2 = 49 . So z = 7 z = 7 .

Thus, for this scenario, there is only one solution ( 5 , 3 , 7 ) (5, 3, 7) for f ( x , y , z ) f(x,y,z) .

Second, for the next scenario, if 3 y 2 = y × 3 y 3y^2 = y\times 3y , then 2 z + n = 3 y 2z+n = 3y and 2 z n = y 2z-n = y .

Then 4 z = 4 y 4z = 4y . z = y z = y , and n = z = y n = z = y . However, if n = y n = y , x = 0 x=0 , so it is contradicted.

Finally, for the last scenario, if 3 y 2 = 3 × y 2 3y^2 = 3\times y^2 , then 2 z n = 3 2z-n = 3 and 2 z + n = y 2 2z+n = y^2 .

Then 2 n = y 2 3 2n = y^2 - 3 . n = y 2 3 2 n = \dfrac{y^2 -3}{2}

Thus, x = n y 2 = y 2 2 y 3 4 = y 2 2 y + 1 4 4 = ( y 1 2 ) 2 1 x= \dfrac{n-y}{2} = \dfrac{y^2 - 2y-3}{4} = \dfrac{y^2 - 2y + 1 -4}{4} = (\dfrac{y-1}{2})^2 - 1

Since x x is prime, there is only one possible factorization: 1 × x = ( y 1 2 ) 2 1 1\times x = (\dfrac{y-1}{2})^2 - 1

Let m = y 1 2 m = \dfrac{y-1}{2} for some integer m m . Then m 2 1 = ( m + 1 ) ( m 1 ) = 1 × x m^2 - 1 = (m+1)(m-1) = 1\times x .

Thus, m + 1 = x m+1 = x , and m 1 = 1 m-1 =1 . Hence, m = 2 m = 2 ; x = 3 x=3 ; and y = 5 y = 5 . And z = 7 z=7 as in the first scenario.

As a result, by checking all possibilities, ( 3 , 5 , 7 ) (3, 5, 7) and ( 5 , 3 , 7 ) (5, 3, 7) the only optimal solutions for f ( x , y , z ) f(x,y,z) . Thus, x y z = 105 xyz = \boxed{105} .

Long solution very bad

How is a long solution very bad Rupayan

Nitin Kumar - 1 year, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...